Spanish L2 Chinese Learners’ Awareness of Morpho-Syntactic Structures in the Reading Comprehension of Splittable Compounds - Lu, Ziming; Dai, Ying; Wu, Yicheng (Frontiers in Psychology, 2022)
Reading comprehension is never considered a simple task in linguists’ view as it requires a full set of linguistic knowledge, such as word decoding, understanding syntactic and morphological structures, and deriving proper meanings from these structures in a given context. Bearing the simple view of reading, the primary goal of this study is to explore whether the split presentation of Chinese splittable compounds influences the recognition of the compounds in second language (L2) Chinese reading comprehension, and how the reading skills, such as word decoding and linguistic comprehension, cooperate to complete this reading comprehension task. Splittable compounds (SCs) in Chinese are typically verbs composed of two constituents with limited separability. The separable property of SCs and their vague morpho-syntactic status are supposed to cause difficulties for L2 Chinese learners in recognizing the compounds. Especially for those whose native language manifests lexical integrity, the split presentation of the compounds may invite the L2 Chinese readers to process them with a mechanism different from that for their non-split forms. To the best of our knowledge, the efforts on investigating this issue are insufficient. In this research, 27 Spanish speaking L2 Chinese learners were invited to complete four tasks: reading and interpreting 6 selected SCs in the split and non-split forms, rating their familiarities with each SC and reporting the syntactic category of the SCs based on their existing linguistic knowledge. The results, based on the error rates in SC recognition and non-parametric tests, showed that the split presentation of SCs did cause challenges for L2 Chinese learners in recognizing the compounds in the reading process, regardless of their Chinese proficiencies. The L2 Chinese participants performed significantly worse in recognizing split SCs in salient Verb-Object structures than recognizing those in unsalient Verb-Object structures. These findings underscore the importance of linguistic comprehension in L2 Chinese in-text word reading comprehension and suggest words as the basic processing units.